PERMASALAHAN PESERTA DIDIK KELAS TINGGI DI SD NEGERI 19 PASAR AMBACANG DURIAN TARUNG KECAMATAN KURANJI PADANG - Maiyeni, Sri - (Bimbingan dan Konseling, 2014)
This research is motivated by condition of high grade learners tend to have problems. The purposeof this research is to describe: 1. The form of personal problems. 2. The form of social adjusment.3. Problems of high grade learners in primary school. This research is quantitative descriptiveresearch. It population are 59 of the learners. For take the example doing by using total samplingtechnique. For this research was take the learners as example research that to be the mainrespondents 30 learners. The instrument that doing in this research refers to questionnaire. Andwhereas for data analysis by using percentage technique. The results of this research revealed that:1. The form of personal problems of learners have many categories. 2. The form of socialadjusment have many categories. 3. The form if learning problems of learners have manycategories.